Large-scale population disappearances and cycling in the white-lipped peccary, a tropical forest mammal - José M. V. Fragoso; André P. Antunes; Kirsten M. Silvius; Pedro A. L. Constantino; Galo Zapata-Ríos; Hani R. El Bizri; Richard E. Bodmer; Micaela Camino; Benoit de Thoisy; Robert B. Wallace; Thais Q. Morcatty; Pedro Mayor; et al. (PLoS ONE, 2022)
Many vertebrate species undergo population fluctuations that may be random or regularly cyclic in nature. Vertebrate population cycles in northern latitudes are driven by both endogenous and exogenous factors. Suggested causes of mysterious disappearances documented for populations of the Neotropical, herd-forming, white-lipped peccary (Tayassu pecari, henceforth “WLP”) include large-scale movements, overhunting, extreme floods, or disease outbreaks. By analyzing 43 disappearance events across the Neotropics and 88 years of commercial and subsistence harvest data for the Amazon, we show that WLP disappearances are widespread and occur regularly and at large spatiotemporal scales throughout the species’ range. We present evidence that the disappearances represent 7–12-year troughs in 20–30-year WLP population cycles occurring synchronously at regional and perhaps continent-wide spatial scales as large as 10,000–5 million km2. This may represent the first documented case of natural population cyclicity in a Neotropical mammal. Because WLP populations often increase dramatically prior to a disappearance, we posit that their population cycles result from over-compensatory, density-dependent mortality. Our data also suggest that the increase phase of a WLP cycle is partly dependent on recolonization from proximal, unfragmented and undisturbed forests. This highlights the importance of very large, continuous natural areas that enable source-sink population dynamics and ensure re-colonization and local population persistence in time and space.